Phosphorus ligands in hydroformylation and hydrogenation: a personal account - Tewari, Tanuja; Kumar, Rohit; Chandanshive, Amol C.; Chikkali, Samir H. (Chemical Record, 2021)
Metal-catalyzed hydroformylation and hydrogenation heavily rely on ligands, among which phosphorous ligands play a pivotal role. This personal account presents a selection of three distinct classes of phosphorous ligands, namely, monodentate meta-substituted phosphinites, bis-phosphites, and P-chiral supramolecular phosphines, developed in our group. The synthesis of these ligands, isolation, characterization, and their performance in transition metal-catalyzed hydroformylation, isomerizing hydroformylation, and asymmetric hydrogenation of olefins is summarized. The state of the art development in iron-catalyzed hydroformylation of alkenes and our contributions to the field is discussed. Use of phosphines enabled iron-catalyzed hydroformylation of alkenes under mild conditions. Thus, this account demonstrates the central role of phosphorus ligands in industrially relevant transformations such as hydrogenation and hydroformylation. The seemingly matured field of ligand discovery still holds significant potential and will steer the field of homogeneous catalysis.
Keywords: Homogeneous catalysis; Hydroformylation; Hydrogenation; Olefins; Phosphorus ligands

Computational insights into the iron-catalyze d magnesium-me diate d hydroformylation of alkynes - Sharma, Himanshu; Tewari, Tanuja; Chikkali, Samir H.; Vanka, Kumar (Journal of Organometallic Chemistry, 2023)
Iron is one of the most abundant transition metals in the earth's crust. It has attracted a lot of attention due to its low toxicity, bio-compatibility, and high natural abundance. Iron-catalyzed hydroamination, hydroalkoxylation, hydrocarboxylation, hydrosilylation, hydroboration, hydrophosphination, hydromagnesiation, and carbonylation reactions have therefore been developed over the past decades. However, despite many experimental and theoretical studies, a complete mechanistic understanding of iron-catalyzed hydrofunctionalisation at the molecular level has not yet been achieved. In this work, through density functional theory (DFT) calculations, we have shown the most feasible path for the hydroformylation of alkynes for an experimentally studied system. We have looked at the iron salt as a precatalyst without any external donor ligand, and the calculations revealed that hydrometalation followed by beta-hydride elimination was favorable over the direct migration of the beta-hydrogen to carbon. Furthermore, our calculations show that the solvent plays an important role in the hydromagnesiation reaction. Furthermore, we have employed an explicit solvent model, where the attachment of one molecule of solvent to the iron center was seen to stabilize the transition states significantly.(c) 2023 Elsevier B.V. All rights reserved.
Keywords: Computational study; Ethylene Assisted Catalysis; EtMgBr Assistance; Explicit Role of Solvent; Hydroformylation; Iron Catalyst

Iron-catalysed highly selective hydroalkoxycarbonylation of alkynes using CO as C1 source - Tewari, Tanuja; Kumar, Rohit; Chikkali, Samir H. (Catalysis Science & Technology, 2023)
Though precious and rare, late-transition metals have been extensively used in metal-catalysed carbonylation reactions in organic transformations. On the other hand, base metals are abundant and cheap, but their practical utilization in carbonylation reactions is rarely explored. Here, we report iron-catalysed hydroalkoxycarbonylation of alkynes to alpha,beta-unsaturated esters in one pot. A readily available iron precursor [Fe2(CO)9] in the presence of a diimine ligand L7 catalyzes the conversion of alkynes to alpha,beta-unsaturated esters under 10 bar CO pressure. This operationally simple protocol tolerates various functional groups and allows facile access to about 40 alpha,beta-unsaturated esters. The synthetic utility of the reaction has been demonstrated by scaling up the reaction to 1 g and by preparing sunscreen/antifungal agents. The kinetic study suggests that the reaction is an approximate 1st order with respect to the iron catalyst, and the initial rate of the reaction is 3.6 x 10-2 M h-1. Mechanistic investigations using NMR spectroscopy indicated the existence of an [Fe-H] intermediate, and control experiments using a radical trapping reagent and EPR revealed the absence of any radical species in the reaction. Precious and rare, late transition metals have been extensively used in carbonylation. An earth abundant iron-catalyst is reported here for hydroalkoxycarbonylation of alkynes in the presence of CO as C1 source.

Iron-catalyzed alkoxylation, dehydrogenative-polymerization and tandem hydrosilylative-alkoxylation - Sen, Anirban; Kumar, Rohit; Tewari, Tanuja; Gonnade, Rajesh G.; Chikkali, Samir H. (Chemistry- a european journal, 2023)
Alkoxylation, hydrosilylative-alkoxylation, and dehydrogenative-polymerization are some of the most widely used transformations in synthetic chemistry. However, these transformations are traditionally catalyzed by precious, and rare late-transition metals. Presented here is a molecularly defined iron complex that catalyzes alkoxylation, tandem hydrosilylative-alkoxylation, and dehydrogenative polymerization of silanes under mild conditions. The iron complex [Fe(CO)(4)(H)(SiPh3)] 1 catalyzes a direct Si-O coupling reaction between an array of silanes and alcohols to produce desired alkoxysilanes in excellent yield, with H-2 as the only byproduct. The iron catalyst tolerates various functional groups and provides access to 20 alkoxysilanes, including essential molecules such as & beta;-citronellol and cholesterol. Further, complex 1 catalyzes the polymerization of renewable diol and silane monomer to produce a renewable and degradable poly(isosorbide-silyl ether). Remarkably, complex 1 catalyzes a tandem hydrosilylative-alkoxylation of alkynes under mild conditions to yield unsaturated silyl ethers. The synthetic utility has been demonstrated by gram-scale alkoxylation and hydrosilylative-alkoxylation reactions.
Keywords: alkoxylation; dehydrogenative polymerization; earth abundant catalysts; hydrosilylative-alkoxylation; Iron Catalyst

Iron-catalyzed magnesium-mediated formal hydroformylation of alkynes and alkenes - Tewari, Tanuja; Kumar, Rohit; Chikkali, Samir H. (ChemCatChem, 2023)
Alkynes and alkenes are routinely converted to corresponding synthetically versatile aldehydes using rhodium-catalyzed hydroformylation. However, rhodium is rare, precious, costly, and depleting at a considerably high rate. Reported here is iron-catalyzed, magnesium-mediated, formal hydroformylation of alkynes and alkenes in the absence of syngas. Readily available FeCl2 in the presence of alkyl magnesium halide, and dimethyl formamide, catalyzes hydroformylation of various alkynes and selectively produces alpha,beta-unsaturated aldehydes in good to excellent conversion. Mechanistic investigations revealed the presence of vinyl magnesium intermediate, the kinetic study disclosed the first-order dependence of the reaction on iron loading, and the control experiment authenticated the iron catalyst's homogeneous nature. The scope of this methodology was amplified, and 20 alkenes were examined. [Fe(acac)(3)] in the presence of ligand, alkyl magnesium halide, and dimethyl formamide catalyzed the hydroformylation of alkenes and displayed good to excellent conversion. An earth-abundant iron catalyst offering a syngas cylinder-free safe alternative to high-pressure hydroformylation has been reported.
Keywords: aldehydes; alkenes; Alkynes; Hydroformylation; iron catalysis

Squarate-tethered enantiomeric Imido-Pd(II) cages for recognition and separation of chiral organic molecules - Jose, Cavya; Sarkar, Meghamala; Rajasekar, Prabhakaran; Tewari, Tanuja; Boomishankar, Ramamoorthy (Inorganic Chemistry, 2023)
Chiral coordination cages have emerged as an efficient platform for enantioselective processes via host-guest interactions. Here, we report an enantiomeric pair of tetrahedral cages of formula [(Pd-3[PO(N(*CH(CH3)Ph)(3)])(4)(C4O4)(6)] supported by chiral tris(imido)phosphate trianions and squarate (C4O4)(2-) linkers. These cages exhibit unusual coordination isomerism for Pd(II)-linker bonds compared with the other Pd(II) cages of this family. Further, they were employed for the recognition and separation of small chiral molecules containing various functionalities. High enantioselectivities of 67 and 41 were found in the case of R-4-hydroxydihydrofuran-2(3H)-one and S-epichlorohydrin, recognized by the R-isomer of the cage. Chiral separation studies showed remarkable enantiomeric excess values of 93 and 85% for S-epichlorohydrin and R-4-benzyl-2-oxazolidinone, respectively, from their racemic mixtures. These studies showcase the potential of coordination cages for enantioselective applications.

Iron in organometallic transformations: a sustainable substitute for noble metals - Kumar, Rohit; Tewari, Tanuja; Chikkali, Samir H. (ChemCatChem, 2024)
Transition metal catalysis plays a pivotal role in chemical synthesis. Noble metals often grab significant attention in organometallic catalysis due to their high reactivity. However, the serious issues associated with these metals such as low abundance, toxicity, geopolitical limitations, and volatile prices are driving the scientific community to discover sustainable alternatives. In this context, iron appears to be the first choice as an alternative metal due to its unique properties, including a range of stable oxidation states, Lewis acidity, high abundance in the earth's crust, and low toxicity. Over the past two decades, substantial progress has been made in iron catalysis. This overview examines the recent developments in iron-catalyzed industrially relevant transformations such as hydroformylation, olefin isomerization, hydrosilylation, hydrophosphination, carbonylation, Wacker-type oxidation, and plastic depolymerization. As witnessed throughout this review, the performance of iron can be significantly altered by suitable ligand selection and by tailoring the electronic and steric properties of the iron center. While noble metals remain the industry work-horse, iron is inching closer and with extensive scientific understanding, it may replace noble metals in the near future. Late transition metals catalyze several reactions and have been the industry work-horse for decades. While, earth abundant metals are rarely used in industrially relevant transformations. In this overview, we examine the recent development in iron-catalyzed industrially relevant reactions such as hydroformylation, olefin isomerization, hydrosilylation, hydrophosphination, carbonylation, Wacker-type oxidation, and plastic depolymerization. Iron is inching closer and may replace noble metals in near future. image
Keywords: Alkene Isomerization; alkyne; Carbonylation; depolymerization; Hydrophosphination; Hydrosilylation; iron catalysis

Iron-catalyzed (E)-selective hydrosilylation of alkynes: scope and mechanistic insights - Sen, Anirban; Tewari, Tanuja; Kumar, Rohit; Vinod, C. P.; Sharma, Himanshu; Vanka, Kumar; Chikkali, Samir H. (Catalysis Science and Technology, 2024)
Iron-catalyzed hydrosilylation of internal alkynes has been rarely reported. Even in these rare cases, additives have been used for the success of the reaction, which often creates a problem for the functional group tolerance of the reaction. Herein, we report an additive-free iron-catalyzed (E)-selective hydrosilylation of internal alkynes in the presence of a phosphine ligand. A low-valent Fe(0) complex [Fe(CO)(3)(BDA)] {[Fe-1]} catalyzed the hydrosilylation of alkynes at 60 to 120 degrees C, exhibited a broad substrate (24 substrates) scope and tolerated different functional groups. The synthetic utility of the reaction was demonstrated by a gram scale experiment, preparing alkenes, and by chemo-selective hydrosilylation. The modus operandi of the reaction has been investigated by i) homogeneity test, ii) radical trapping experiments, iii) X-ray photoelectron spectroscopy, and iv) by preparing a Fe(II) complex as catalyst control. These mechanistic investigations revealed a two-electron pathway for the hydrosilylation of alkynes. In addition, kinetic investigations were undertaken to shed light on the rates of the reaction. Kinetic studies suggest the absence of an induction period, and the reaction is first order with respect to the concentration of iron catalyst [Fe-1] and zeroth order with respect to the substrate (alkyne). The Hammett plot suggests that strongly electron-withdrawing groups on the alkyne favour the hydrosilylation reaction. Meanwhile Eyring analysis suggests that the rate-determining step likely involves an associative pathway. Based on the findings of the mechanistic and kinetic investigation, a plausible Chalk-Harrod-type mechanism is likely to be operative. The proposed mechanism is substantiated by computational investigations, which suggested that the Chalk-Harrod mechanism is kinetically more favored by 15.8 kcal mol(-1) over the modified Chalk-Harrod mechanism.

Iron-catalyzed chemoselective reduction of enimines to N-Allylic amines via hydrosilylation - Tewari, Tanuja; Shaikh, Maulali H.; Sharma, Himanshu; Vanka, Kumar; Chikkali, Samir H. (Asian Journal of Organic Chemistry, 2025)
Chemoselective hydrosilylation of unsaturated imines is challenging as the two double bonds compete for the reaction. Here in, we report an iron-catalyzed chemoselective hydrosilylation of enimines leading to the generation of allyl amines in the presence of phosphine ligand. A low-valent Fe(0) complex [(BDA)Fe(CO)3] catalyzed the hydrosilylation of enimine at room temperature and exhibited broad substrate scope including a variety of enimine (cinnamylimine, allylimine) and ketimine. Mechanistic investigations revealed that the reaction proceeds through an oxidative addition of the silane compound, leading to the formation of an iron hydride intermediate. Subsequently, a two-electron pathway facilitates the hydrosilylation of the enimine substrate. This has been supported by preparing a well-defined Fe(II)-silane complex and using it as a catalyst control. Based on experimental and computational investigations, a plausible Chalk-Harrod-type mechanism is proposed.
Keywords: Cinnamyl amine; Imine hydrosilylation; iron catalysis; Iron hydride; Phosphine

Rh-Catalyzed Asymmetric Hydroformylation: The Case of Substituted and Heterocyclic Olefins - Tewari, Tanuja; Khopade, Kishor V.; Chikkali, Samir H. (ChemCatChem, 2025)
Asymmetric hydroformylation (AHF) of prochiral alkenes is an efficient way to synthesize optically active aldehydes, which are versatile chiral building blocks for pharmaceuticals, agrochemicals, and other fine chemicals. The purpose of this review is to take stock of developments in the last decade and shed light on the understanding of the field of AHF. So far, most of the literature methods focused on the use of Rh-based catalysts, due to high catalytic activity and excellent chemoselectivity for the aldehydes. Several chiral phosphorus ligands have been successfully developed for Rh-catalyzed AHF reactions. This review examines the role of the substrate/olefins in AHF. Several different types of ``mono-substituted'' terminal olefins (functionalized/nonfunctionalized) with a variety of chiral ligands have been investigated, which show high activity and excellent ee of up to 99%. The AHF of ``di-substituted'' and ``tri-substituted'' olefins is rarely reported. This review summarizes the evolution of chiral ligands for AHF. It discusses the progress made in desymmetrizing hydroformylation. In addition, it highlights important developments in AHF carried out with and without syngas. These advances span a wide variety of alkenes. Additionally, the review offers future approaches in the field of AHF for the synthesis of optically active aldehydes.
Keywords: Asymmetric hydroformylation; Asymmetric transfer hydroformylation; Chiral ligands; Desymmetrizing hydroformylation; Substituted alkenes